2019
DOI: 10.1186/s13223-019-0357-y
|View full text |Cite
|
Sign up to set email alerts
|

Allergen sensitization pattern of allergic adults and children in southern China: a survey based on real life data

Abstract: Background Allergic diseases are increasing yearly. We aimed to evaluate the difference in allergen sensitization pattern between adults and children in southern China by analyzing a large sample size of real-life data, and to provide the evidence for formulating the prevention and management strategies. Methods Retrospective analysis was conducted on 39,813 serum allergen-specific IgE (sIgE) results collected in southern China from January to December in 2017. Sensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 22 publications
3
33
3
Order By: Relevance
“…In the past decades, lots of studies were conducted to investigate the allergens sensitization patterns. Luo et al [17] reported that house dust mite was the most common allergen in southern China, which was consistent with our findings. Lee [18] reported that different aeroallergens had different effects on the upper and lower airways of inner-city children in Korea, aeroallergen sensitization was closely related to clinical presentation.…”
Section: Discusssionsupporting
confidence: 93%
“…In the past decades, lots of studies were conducted to investigate the allergens sensitization patterns. Luo et al [17] reported that house dust mite was the most common allergen in southern China, which was consistent with our findings. Lee [18] reported that different aeroallergens had different effects on the upper and lower airways of inner-city children in Korea, aeroallergen sensitization was closely related to clinical presentation.…”
Section: Discusssionsupporting
confidence: 93%
“…The most common aeroallergen detected in our study was artemisia (14.47%), which is not consistent with the highest dust mite reported in other Chinese regions [5-9]. Moreover, the positive rate of artemisia was mounting up from spring to autumn and reached its maximum (29.09%) in August, which is the growing season of Artemisia.…”
Section: Discussioncontrasting
confidence: 95%
“…Allergic bronchopulmonary aspergillosis is a pulmonary disease caused by A fumigatus , and pathogenesis is caused by the allergic response against A fumigatus colonizing the airways rather than saprophytic or invasive of the fungi 7,8 . When patients with ABPA are exposed to fungi in the environment, they display repeated wheezing and dyspnea; this condition can even be life‐threatening in severe cases 9 .…”
Section: Introductionmentioning
confidence: 99%